ASSERT (Acute Sacral inSufficiEncy fractuRe augmenTation): Perceptions in the Assessment and Treatment of Pubic Rami and Sacral Fragility Fractures Amongst Healthcare Professionals in Geriatric Medicine and Surgery—A Qualitative Study. (8th July 2021) - Sahota, Opinder; Leighton, Paul; Cameron, Maribel; Taylor, Rachael; Ong, Terence; Drummond, Avril; Hendrick, Paul; Quraishi, Nasir; Salem, Khalid
Background: Pubic rami fragility fractures are common in older people and result in significant morbidity and increased mortality. Co-existing fractures of the sacrum are common, but routinely missed. The aim of the study was to explore the perceptions in the assessment and treatment of pubic rami and sacral fragility fractures amongst healthcare professionals. Methods: We interviewed 14 participants about their experience in the assessment and treatment of patients presenting with pubic rami fragility fractures. Data was analyzed using an inductive thematic approach. Results: The majority of patients presenting with a pubic rami fragility fracture were managed by geriatricians. However, many of the geriatricians were not aware that these fractures have a high association with co-existing sacral fragility fractures. Furthermore, they were not aware of the limitations of standard x-ray imaging, nor of the potential benefits of surgical intervention for sacral fragility fractures. Spinal surgeons recommended that early, more specialist imaging in patients with pubic rami fragility fractures failing to mobilize, would change clinical management, if found to have a coexisting sacral fragility fracture, amenable to surgical intervention. Conclusions: The awareness, assessment and management of sacral fragility fractures in patients presenting with pubic rami fragility fractures is poor amongst healthcare professionals in geriatric medicine. Spinal surgeons in this study advocate early further imaging and surgical intervention in patients confirmed to have a concomitant sacral fragility fracture who are failing to mobilize.